Metabolic reprogramming of tumor-associated neutrophils in tumor treatment and therapeutic resistance - Lin, Jun; He, Xian-Lu; Zhang, Wei-Wei; Mo, Chun-Fen (Frontiers in Cell and Developmental Biology, 2025)
Tumor-associated neutrophils (TANs), pivotal immune cells within the tumor microenvironment (TME), exhibit dual potential in both pro- and anti-tumorigenic effects. These cells display remarkable heterogeneity and plasticity within the TME, adapting to hypoxic and nutrient-deprived conditions through metabolic reprogramming while critically influencing tumor progression, metastasis, and immune evasion. The metabolic reprogramming of TANs not only modulates their functional phenotypes but also reshapes tumor biological behaviors and therapeutic responses by regulating metabolic intermediates and cellular interactions within the TME. Therefore, elucidating the mechanisms underlying TANs metabolic reprogramming has significant implications for deciphering the molecular basis of tumorigenesis, identifying novel therapeutic targets, and optimizing immunotherapeutic strategies. This review systematically summarizes current knowledge regarding metabolic reprogramming mechanisms of TANs in the TME and their impact on tumor progression. We particularly focus on: 1) TAN-specific alterations in glucose, lipid, and amino acid metabolism within the TME; 2) Emerging immunotherapeutic strategies targeting TANs metabolic pathways; 3) Recent advances in understanding TAN-mediated immune evasion and therapy resistance. Furthermore, this review discusses potential challenges and corresponding solutions in targeting TANs metabolic reprogramming for therapeutic intervention, aiming to provide novel insights for advancing cancer immunotherapy.